Proceso de atención de enfermería en gestante de 28 semanas con óbito fetal. - Peñafiel Cortez, Anderson Daniel (2024)
Stillbirths are occurring very frequently in several countries. A fetal death is defined as one that occurs after 20 weeks of gestation or when the fetal weight is greater than 500g and the gestational age is not clear. It is one of the most common adverse outcomes worldwide. This case study aimed to develop the Nursing Care Process (PAE) in a 28-week pregnant woman with fetal death. This complication, based on the weeks of gestation, can be classified into the following categories: early fetal death, which ranges from 22 to 28 weeks; in the late stage, which occurs between 29 and 36 weeks; and term, which is defined as being after 37 weeks. In this clinical study, we seek to highlight the importance of the role of the nurse within the care process of patients diagnosed with fetal death.